Non-valvular atrial fibrillation patients with none or one additional risk factor of the CHA2DS2-VASc score - Lip, Gregory Y. H.; Skjøth, Flemming; Nielsen, Peter B.; Larsen, Torben Bjerregaard (Thrombosis and Haemostasis, 2015)
Oral anticoagulation (OAC) to prevent stroke has to be balanced against the potential harm of serious bleeding, especially intracranial haemorrhage (ICH). We determined the net clinical benefit (NCB) balancing effectiveness and safety of no antithrombotic therapy, aspirin and warfarin in AF patients with none or one stroke risk factor. Using Danish registries, we determined NCB using various definitions intrinsic to our cohort (Danish weights at 1 and 5 year follow-up), with risk weights which were derived from the hazard ratio (HR) of death following an event, relative to HR of death after ischaemic stroke. When aspirin was compared to no treatment, NCB was neutral or negative for both risk strata. For warfarin vs no treatment, NCB using Danish weights was neutral where no risk factors were present and using five years follow-up. For one stroke risk factor, NCB was positive for warfarin vs no treatment, for one year and five year follow-up. For warfarin vs aspirin use in patients with no risk factors, NCB was positive with one year follow-up, but neutral with five year follow-up. With one risk factor, NCB was generally positive for warfarin vs aspirin. In conclusion, we show a positive overall advantage (i.e. positive NCB) of effective stroke prevention with OAC, compared to no therapy or aspirin with one additional stroke risk factor, using Danish weights. ‘Low risk’ AF patients with no additional stroke risk factors (i.e. CHA2DS2-VASc 0 in males, 1 in females) do not derive any advantage (neutral or negative NCB) with aspirin, nor with warfarin therapy in the long run.Note: The review process for this manuscript was fully handled by Christian Weber, Editor in Chief.
Keywords: Net clinical benefit; mortality; stroke; bleeding